Evaluation of pathogenicity variation between two Erwinia species in apples and their population using a duplex real-time PCR method - Lee, Mi-Hyun; Balaraju, Kotnala; Choi, Hyo-Won; Lee, Yong Hwan (Frontiers in Microbiology, 2025)
Fire blight and black shoot blight diseases, caused by Erwinia amylovora and Erwinia pyrifoliae, respectively, continue to spread several areas in Korea, despite intensive efforts by the government to control diseases. The distribution pattern of fire blight and black shoot blight is different from each other in Korea. Consequently, it is required to investigate the pathogenicity of E. amylovora and E. pyrifoliae in apple trees. The disease severity of fire blight and black shoot blight was compared in this study by an artificial inoculation of E. amylovora and E. pyrifoliae suspensions into the abaxial veins of apple leaves and measuring their pathogenicity at varying temperatures. Furthermore, disease severity was assessed by inoculating E. amylovora and E. pyrifoliae in apple flowers and assessing their pathogenicity at various temperatures. The E. amylovora-inoculated flowers displayed greater disease index than E. pyrifoliae-inoculated flowers at temperatures ranging from 18°C to 25°C. Upon examining the population sizes of E amylovora and E. pyrifoliae in flowers using a real-time polymerase chain reaction (PCR), the Ct value of E. amylovora was found to be lower in the style including stigma and hypanthium than the Ct value of E. pyrifoliae, except at 18°C. Hypanthium contained E. amylovora TS3128 and E. pyrifoliae YKB12327 at >107 and 105 CFU/mL, respectively at 15°C. Furthermore, in this study, we investigated the population size of E. amylovora and E. pyrifoliae in apple flowers in relation to temperature in order to clarify the differences in their pathogenicity.